Navigating Turn-Taking and Conversational Repair in an Online Synchronous Course - Yvonne Earnshaw (Online Learning, 2017)
In face-to-face conversations, speaker transitions (or hand-offs) are typically seamless. In computer mediated communication settings, speaker hand-offs can be a bit more challenging. This paper presents the results of a study of audio communication problems that occur in an online synchronous course, and how, and by whom, those problems are resolved. Data were collected from chat transcripts and audio transcripts from a graduate level discourse and conversation analysis course that used WebEx, an audioconferencing software application that also has a chat channel. Using a conversational analysis approach, data were analyzed to identify when speaker hand-offs occurred to determine related patterns of confirmation strategies and repair sequences. Findings showed several different approaches to smooth speaker hand-offs. In cases where hand-offs were not smooth, corrections were attempted by either fixing the problem or moving on. There were also instances in which parties encountered technical difficulties with the audio or Internet connectivity. Parties used the chat channel to indicate they were having trouble. The instructor’s role was to troubleshoot, call upon students, and move the discussion along. This study provides some insight on how chat can be used in a discussion-based, online synchronous course to identify technical difficulties with a called-upon speaker and how the correction is made.